A Preliminary Study on the Effects of Photoinitiator and UV Curing Exposure Time to the Mechanical and Physical Properties of the Epoxy and Vynil Ester Fiber Glass Laminated Composites - Junid , Ramli; Abd Salam, Hadi; ABD RAZAK , JEEFFERIE; Mahat, Mohd Muzamir (IJENS, 2010)
Abstract—Ultra-violet (UV) curing process is introduced in the curing of polymer matrix composites (PMC) for the application in producing bullet proof vest. Two types of adhesives or matrix materials were used: epoxy and vinyl ester. Each of them were mixed together with different types of photoinitiator; Bisacyl Phosphine Oxide (BaPO) and Alpha Hydroxyl Ketone Peroxide (AHK) at 1.0 and 10.0 per hundred of resin (phr) from the total proportion of the mixture. Sandwich construction of the PMC was done by hand lay-up process where the mixture was wiped on the fiber layers. Samples were then cured under various duration times which are 3, 6, 9 and 12 minutes to compare the quality of composites under the exposure of the UV light. The laminate was then tested to determine its characteristics of physical properties and its behavior to applied loads. Morphological observation through Scanning Electron Microscope (SEM) was performed in order to evaluate the quality of adhesion between each fiber layer and matrix wetting behavior. Vinyl ester is not recommended to be used as the matrix since two days is required to make it fully cured unlike epoxy which was cured rapidly once exposed under UV light. The physical testing shows that optimum density for the effect of photoinitiator obtained at 1.0phr for epoxy and 10.0phr for vinyl ester. This could give benefit to the manufacturer since it gives lower weight compared to virgin matrix materials. On the other hands, the effect of curing time shows the optimum result for density was obtained at 12 minutes of curing time. The effect of photoinitiator to the tensile strength shows optimum results at 1.0 phr for both epoxy and vinyl ester while curing time between 6 to 9 minutes is proposed to be optimum for the exposure of composites under UV light. Effect of photoinitiator to the hardness of the PMC is found optimum at the present of 1.0 phr for both matrix materials and optimum at 3 minutes to be exposed under UV light for the effect of curing time.